Application of Open Proportional System in Post Amendment Legislative Elections Basic Law of the Republic of Indonesia Year 1945 - Jamaluddin Jamaluddin; Ellydar Chaidir; Efendi Ibnu Susilo (Green Publisher Indonesia, 2021)
This study aims to examine how the concept of the application of the Open Proportional System in the Legislative Elections After the Amendment to the 1945 Constitution of the Republic of Indonesia is applied. This study uses a normative juridical method based on primary and secondary legal materials. The form of the results of this research is descriptive analysis, where the results of the research provide an objective description of the concept of the application of the Open Proportional System in the Legislative Elections After the Amendment to the 1945 Constitution of the Republic of Indonesia. The approaches in this study are: statute approach, and conceptual approach. In tracing legal materials, the author uses the Research library, and uses qualitative analysis. The results show that the application of the open proportional system in the legislative elections after the amendment to the 1945 Constitution of the Republic of Indonesia varies, the 2004 election with a limited open proportional system using a BPP value of 100%, the 2009 and 2014 elections applying a pure open proportional system using the hare quota method and the 2019 election applying the system pure open proportional with sound conversion method using sainte lague system. The open proportional system is also able to present a variety of electoral winning parties.